Pembuatan Virtual Map pada Gedung P lantai 2 Universitas Kristen Petra - Roy Darsono Angky; Liliana - -; Gregorius Satiabudhi (Jurnal Infra, 2014)
The development and competition at the University in Indonesia is very strict. Petra Christian University is the University’s long-standing and well known to many people in Indonesia. Matriculant also want to know about condition and facilities inside of the University. Difficulties that exist in the prospective student who resides outside the island, because it will be spent much accomodation cost to visit the University. This program is expected to help to see Petra Christian University in virtual map.In the making of program, have some research about position and shape each object in the building. It’s expected virtual map can be realistic enough. 3d object has been make with AutoCad program for the precision in size. After that, 3dsMax support for give some material in object. It also give some collision, so when user walk around in the bulding it will not be outside from the building.The result from this program is every object shape and position close enough. Time constraints become a major problem from making this program, so some of the details can’t be complete. All of the laboratorium in the 2nd floor already done, but the main stairway in P building 2nd floor and the other minor object haven’t done yet.lack of this program is must use high specification of computer. Because the result from this program is too big and need high recommendation.